SECURITY ANALYSIS OF VARIOUS HASH ALGORITHMS FOR AUTHENTICATION UNDER HARDWARE CONSTRAINED ENVIRONMENT - Husain, Rashid; Khan , Rabia; Tyagi, Rajesh Kumar (International Journal of Engineering Technologies and Management Research, 2020)
Protecting passwords is now a big challenge because users want to do all types of work online via user-friendly devices such as mobile, tablets etc. Now, It is difficult to implement the secure heavy weight algorithms such as AES, RSA etc. in hardware constrained devices. It has been observed that users want all types of security services in an online public environment. Authentication is the first and foremost step to enhance security. Various applications are available for real time authentications such as keyless car entry and opening home-doors through security algorithms under remote keyless entry System (RKES). Now, it is the demand of the time to implement the lightweight security algorithms without compromising the security. In order to fulfill this challenge, this paper proposed a strong model for enhancing authentication security. In this work, strong authentication techniques are implemented with the light weight algorithms. This model received good comparison results.